Microbial inoculation elicited changes in phyllosphere microbial communities and host immunity suppress Magnaporthe oryzae in a susceptible rice cultivar. (April 2021) - Thapa, Shobit; Prasanna, Radha; Ramakrishnan, Balasubramanian; Mahawar, Himanshu; Bharti, Asha; Kumar, Aundy; Velmourougane, Kulandaivelu; Shivay, Yashbir Singh; Kumar, Arun
Abstract: The hemibiotrophic fungal pathogen Magnaporthe oryzae causes serious crop losses in rice. As phyllospheric microbes share a common habitat with this foliar pathogen, they can be deployed as the change-agents for engineering desired phyllospheric microbial communities to inhibit the disease progression. Comparative evaluation of a set of native microbes, when applied as foliar spray or soil drench was undertaken, showed significant interactive effects on the concentrations of chlorophyll a and b, and carotenoids. A significant enhancement was recorded in the activities of chitosanase, β-1, 3-endoglucanase and β-1, 4-endoglucanase (CMCase) in the disease challenged plants, as compared to healthy plants. Among the treatments, Bacillus sp. (B1) inoculation recorded lowest values of the activities of all three hydrolytic enzymes, while Bacillus sp. (B4) and Nostoc-Anabaena consortium (C1) led to 30–60% decreases, both as foliar and soil drench modes of application. Distinct changes in the abundances of eubacterial and phylum Cyanobacterial 16S rRNA gene copies, nifH and bacterial amoA illustrated the significance of foliar over the soil drench method. The nifH gene copies were significantly higher due to the foliar method of Calothrix sp. (C2) inoculation, and values were significantly at par values with both the soil drench application of B1 ( Bacillus sp.) and C1 ( Nostoc-Anabaena consortium) treatments. This study illustrates the significance of the root-shoot linkages in the effective biocontrol of these promising, indigenous microbes, applied as soil drench or foliar agents, which can be useful in abating the incidence of the fungal pathogen in an environment –friendly manner. Graphical abstract: Image 1 Highlights: Microbes evaluated as foliar spray or soil drench against Magnaporthe oryzae . Foliar and soil drench of Bacillus sp. lowered hydrolytic enzymes activities. Foliar and soil drench altered nifH and bacterial amoA gene abundances. nifH gene copies significantly higher in foliar inoculation of Calothrix sp. (C2). Root-shoot continuum important in effective biocontrol using microbes.